Changes in mitochondrial stability during the progression of the Barrett's esophagus disease sequence. Issue 1 (December 2016) - O'Farrell, N.; Feighery, R.; Picardo, S.; Lynam-Lennon, N.; Biniecka, M.; McGarrigle, S.; Phelan, J.; MacCarthy, F.; O'Toole, D.; Fox, E.; Ravi, N.; Reynolds, J.; et al.
Abstract Background Barrett's esophagus follows the classic step-wise progression of metaplasia-dysplasia-adenocarcinoma. While Barrett's esophagus is a leading known risk factor for esophageal adenocarcinoma, the pathogenesis of this disease sequence is poorly understood. Mitochondria are highly susceptible to mutations due to high levels of reactive oxygen species (ROS) coupled with low levels of DNA repair. The timing and levels of mitochondria instability and dysfunction across the Barrett's disease progression is under studied. Methods Using an in-vitro model representing the Barrett's esophagus disease sequence of normal squamous epithelium (HET1A), metaplasia (QH), dysplasia (Go), and esophageal adenocarcinoma (OE33), random mitochondrial mutations, deletions and surrogate markers of mitochondrial function were assessed. In-vivo and ex-vivo tissues were also assessed for instability profiles. Results Barrett's metaplastic cells demonstrated increased levels of ROS (p  < 0.005) and increased levels of random mitochondrial mutations (p  < 0.05) compared with all other stages of the Barrett's disease sequence in-vitro. Using patient in-vivo samples, Barrett's metaplasia tissue demonstrated significantly increased levels of random mitochondrial deletions (p  = 0.043) compared with esophageal adenocarcinoma tissue, along with increased expression of cytoglobin (CYGB) (p  < 0.05), a gene linked to oxidative stress, compared with all other points across the disease sequence. Using ex-vivo Barrett's metaplastic and matched normal patient tissue explants, higher levels of cytochrome c (p  = 0.003), SMAC/Diablo (p  = 0.008) and four inflammatory cytokines (allp values <0.05) were secreted from Barrett's metaplastic tissue compared with matched normal squamous epithelium. Conclusions We have demonstrated that increased mitochondrial instability and markers of cellular and mitochondrial stress are early events in the Barrett's disease sequence.